2019
DOI: 10.1136/sextrans-2018-053906
|View full text |Cite
|
Sign up to set email alerts
|

Potential HIV transmission risk among spouses: marriage intention and expected extramarital male-to-male sex among single men who have sex with men in Hunan, China

Abstract: ObjectiveThe HIV epidemic in China is shifting from the high-risk groups of men who have sex with men (MSM), injection drug users and sex workers to the general population, and sexual contact among spouses is assumed to be one route of transmission. Our objective was to determine the intention to marry and the expected extramarital male-to-male sex among single Chinese MSM, in order to estimate the potential HIV transmission risk among MSM living with HIV and their female spouses.MethodsWe conducted a web-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 17 publications
4
18
0
Order By: Relevance
“…This study found that the majority of MSM were unmarried, which is consistent with the previous studies [8,10,14,27,30]. The first reason may be that same-sex marriage is not recognized by the law and the secular in China [28], while some studies have found that attitudes towards sex and gender diversity have become more tolerant in China, and more MSM will remain single or live with gay partners [29]. Second, some people hold the belief that not getting married is responsible for themselves and will not cause harm to female partners [31].…”
Section: Social Demographic Factors Related To Hiv Infectionsupporting
confidence: 90%
See 3 more Smart Citations
“…This study found that the majority of MSM were unmarried, which is consistent with the previous studies [8,10,14,27,30]. The first reason may be that same-sex marriage is not recognized by the law and the secular in China [28], while some studies have found that attitudes towards sex and gender diversity have become more tolerant in China, and more MSM will remain single or live with gay partners [29]. Second, some people hold the belief that not getting married is responsible for themselves and will not cause harm to female partners [31].…”
Section: Social Demographic Factors Related To Hiv Infectionsupporting
confidence: 90%
“…In this study, MSM is mainly young people, which is similar to the research results of many literatures [8,10,13,14,[27][28][29]. Qin et al [7] found that most HIV infection cases in China occurred in MSM aged 20-39, which indicates that HIV may be more prevalent among young MSM population in the sexually active period [13].…”
Section: Social Demographic Factors Related To Hiv Infectionsupporting
confidence: 86%
See 2 more Smart Citations
“…The results of this study indicate that the annual testing behavior of married MSM is not as good as that of single MSM. A study in China showed that under parental or social pressure, nearly half (48.9%) of men who had sex with men chose to marry women, and 91% of them reported that they would practice homosexual behavior after marriage [19]. This behavior may expand the spread of HIV from MSM to the general population or the next generation.…”
Section: Discussionmentioning
confidence: 99%